Herd Immunity Against Rabies Among Dogs in Ambon - Astri D T agueha D Tagueha; Setyawan Budiharta; Heru Susetyo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
The objectives of this study were to reveals factors associated with level of herd immunity against rabies. Four hundred and eighteen blood samples were collected from five subdistricts and 14 villages using stratified and household cluster methods. The result in ELISA test is ≥ 0,5 IU/ml, dog titers sample was stated as protective to rabies. The result showed that the prevalence of protective antibody titers was very low i.e. 3.35%. Linear regression analysis reveals subdistrict of Nusaniwe, subdistrict of Baguala, dog owner education, post-vaccination period of 0 - 6 months, sex, and dogs kept as a guard house contribute to protective level of antibody titers. Unweighted logistic regression revealed that subdistrict of Baguala (OR = 0.05), subdistrict of Sirimau (OR = 0.09), dog kept as a guard house (OR = 3.96), dog owner education (OR = 12.29), and post-vaccination period of 0 - 6 months (OR = 27.08) are significantly associated with dog's immunity . V accination programs need to be improved by considering the four factors that emerged in these two regression results.Keywords : rabies, level of dog's immunity , ELISA, Ambon, post-vaccination